Numerical studies on explosion hazards of vehicles using clean fuel in short vehicular tunnels. (January 2021) - To, C.W.; Chow, W.K.; Cheng, F.M.
Highlights: Heavy traffic load in short vehicular tunnels (SVT) in densely populated cities. Concern for fire safety of SVT due to increasing use of clean fuels in vehicles. Explosion hazard of a taxi using liquefied petroleum gas (LPG) in a SVT was studied. LPG leaking into the concealed space beneath tunnel floor level of SVT was simulated. Appropriate protection measures should be provided to ensure the safety of SVT. Abstract: Short vehicular tunnels (SVT) with heavy traffic are commonly constructed in urban areas of densely populated cities of the Asia-Oceania Region. The introduction of vehicles using clean fuel poses new concerns on the fire safety of existing road tunnels. The explosion of a taxi using Liquefied Petroleum Gas (LPG) occurred in a garage, alarming the need for protecting existing road tunnels against hazards in using clean energy. In this paper, explosion hazards of an LPG taxi in a section of SVT were studied by using Computational Fluid Dynamics (CFD) Flame Acceleration Simulator (FLACS). The scenario of LPG leaking into the concealed space beneath the tunnel floor level of SVT through vents at the road side is simulated. A full tank of LPG would completely be released in about 231 s. The leaked LPG in the concealed space is ignited 19 s after the complete release, i.e. at t = 250 s. Predicted results on explosion pressure and temperature illustrate that appropriate protection measures should be provided to ensure the safety of SVT. Results also suggest that the existing fire safety codes for SVT should be revised by including an explosion analysis of LPG taxis.